2017
DOI: 10.14740/jocmr3038w
|View full text |Cite
|
Sign up to set email alerts
|

Ipragliflozin Improves Glycemic Control and Decreases Body Fat in Patients With Type 2 Diabetes Mellitus

Abstract: BackgroundIpragliflozin, a sodium-glucose transporter 2 inhibitor, was administered to patients with type 2 diabetes mellitus for 24 weeks to evaluate its effect on glycemic control and body composition.MethodsThis was an investigator-initiated multicenter prospective intervention study in which ipragliflozin (50 mg) was administered once daily and glycemic control, blood pressure, body weight (BW), body composition (measured by a biological impedance method), the lipid profile, and adverse events were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…These findings were comparable to the changes in AST, ALT, and γ-GTP levels (-2.4, -5.8, and -11.3 U/L, respectively) previously reported in a pooled analysis of five randomized controlled trials in patients treated with ipragliflozin [10]. Furthermore, the decrease in ALP (-8.9 U/L) observed in our study is in line with the findings of Kawata et al [24], who reported a -11.4 U/L change in ALP at 12 weeks after initiation of ipragliflozin therapy in the multicenter ASSIGN-K trial patient population. A clinically significant improvement in liver function parameters was only observed in the subgroup with abnormal liver function.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were comparable to the changes in AST, ALT, and γ-GTP levels (-2.4, -5.8, and -11.3 U/L, respectively) previously reported in a pooled analysis of five randomized controlled trials in patients treated with ipragliflozin [10]. Furthermore, the decrease in ALP (-8.9 U/L) observed in our study is in line with the findings of Kawata et al [24], who reported a -11.4 U/L change in ALP at 12 weeks after initiation of ipragliflozin therapy in the multicenter ASSIGN-K trial patient population. A clinically significant improvement in liver function parameters was only observed in the subgroup with abnormal liver function.…”
Section: Discussionsupporting
confidence: 93%
“…Second, these measurements have rarely been included in randomized controlled trials. A single‐arm study with ipragliflozin showed a significant reduction in total muscle mass compared with baseline, as assessed with BIA. Third, the present patients were relatively older and leaner than those in previous studies.…”
Section: Discussionmentioning
confidence: 43%
“…In the present study, 80% of BW reduction resulted from fat mass reduction (Figure ). In the previous studies based on Japanese populations, 71–85% of BW reduction achieved with SGLT2 inhibitors resulted from fat loss as assessed with BIA, and the reduction rates seemed to be dependent on the “treatment period.” The studies showed a trend toward a greater reduction rate at 6 or 12 months than that at 3 months. That would be another reason for the minor difference in the fat reduction rate in the same population.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The safety and efficacy of ipragliflozin in type 2 diabetes patients has been shown through clinical trials and post‐marketing surveys. Several studies have shown that ipragliflozin lowers blood glucose levels in an insulin‐independent fashion, and hence is expected to be efficacious in type 1 diabetes, as well as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%